Lactifluus hezhangensis sp. nov. (Russulaceae, Russulales) from Southwest China - Chen, A-Min; Pei, Yun; Wen, Ting-Chi; Hapuarachchi, Kalani Kanchana; Xu, Xiu-Hong; Zhang, Wan-Ping (Phytotaxa, 2022)
Lactifluus is an ectomycorrhizal, genetically diverse genus which consists of many species complexes. The genus is widely distributed in the tropics and drives important ecological and economic functions. However, its generic relations are poorly known and the diversity is mostly unexplored. In this study, we propose a new species, Lactifluus hezhangensis sp. nov. belongs to Lf. sect. Gerardii, from Guizhou Province, China. Lactifluus hezhangensis is characterized by a rugose and dark brown pileus, pruinose near center; white to cream lamella, and small basidiospores (4.79) 5.06–7.22 (7.30) × (4.67) 4.68–6.20 (6.59) μm). The phylogenetic analyses based on combined three-gene fragments of ITS + LSU + RPB2 confirmed that the new species is distinct from other Lactifluus species. Furthermore, the new species is described with color photographs and compared with similar taxa. We provide a phylogeny for Lf. sect. Gerardii based on ITS, LSU + RPB2 sequence data and the taxonomic status of the new species is briefly discussed.